Consequential Life Cycle Assessment of Policy Vulnerability to Price Effects. (16th October 2013) - Rajagopal, Deepak
Summary The application of life cycle assessment (LCA) in a policy context highlights the need for a "consequential" LCA (CLCA), which differs from an "attributional" LCA (ALCA). Although CLCA offers some advantages over ALCA, such as a capacity to account for emissions resulting from both substitution and price effects, it entails additional assumptions and cost and may yield estimates that are more uncertain (e.g., estimates of impact of biofuel policies on greenhouse gas [GHG] emissions). We illustrate how a CLCA that relies on simple partial equilibrium models could provide important insights on the direction and magnitude of price effects while limiting the complexity of CLCA. We describe how such a CLCA, when applied early in the policy life cycle, could help identify policy formulations that reduce the magnitude of adverse price effects relative to the beneficial substitution effect on emissions because—as the experience with biofuel regulations indicates—regulating price effects is costly and controversial. We conclude that the salient contribution of CLCA in the policy process might lie in warning policy makers about the vulnerabilities in a policy with regard to environmental impact and to help modify potentially counterproductive formulations rather than in deriving the precise estimates for uncertain variables, such as the life cycle GHG intensity of product or average indirect emissions.